On derived π-length of a finite π-solvable group with supersolvable π-Hall subgroup - Monakhov, V.S.; Gritsuk, D.V. (Algebra and Discrete Mathematics, 2013)
It is proved that if π-Hall subgroup is a supersolvable group then the derived π-length of a π-solvable group G is at most 1 + maxr∈π lαr(G), where lαr(G) is the derived r-length of a π-solvable group G.